Analisis Kandungan Merkuri (Hg) dan Kadar Klorofil Lamun Enhalus Acoroides Di Perairan Marlosso dan Nametek Kabupaten Buru Provinsi Maluku - Natsir, Nur Alim; Selanno, Debby A.J.; Tupan, Ch I; Male, Yustinus T. (INSTITUT AGAMA ISLAM NEGERI AMBON, 2020)
Seagrass is a type of vegetation that is able to live and develop well in coastal areas and is a habitat for several types of marine animals,such as sea cucumbers, sea urchins, starfish and sea urchins. Seagrass is an organism that is susceptible to pollution of the coastal environment such as mercury (Hg) so that it has an impact on the chlorophyll content of seagrass leaves. This study aims to determine the content of heavy metal Hg and its relationship with the chlorophyll content of seagrass Enhalus acoroides in the waters of Marlosso and Nametek in Buru District Maluku Province. The study was conducted in May 2018 and laboratory analysis was conducted in June 2018. Samples were taken at two stations namely Nametek Beach and Muos Sungai Marlosso. The results showed that the content of heavy metal Hg in roots> rhizoma> seagrass leaves. The content of heavy metals and seagrass chlorophyll content has a negative correlation where the Hg metal has a correlation of (r = - 0.97) and indicates that the higher the content of heavy metals will reduce the seagrass chlorophyll content